Peran Brand Image dan Brand Trust Memediasi Pengaruh Influencer Endorsement Terhadap Niat Pembelian - Mar'atus Sholikah (Jurnal Dinamika Ekonomi & Bisnis, 2023)
The purpose of this research is to examine the impact of brand image, price, and product quality on consumer satisfaction on Madu AG business in Tulungagung Regency. The associative method with quantitative approach were used in this research. The sample of 60 respondents was obtained from the Madu AG consumer population in Tulungagung Regency using purposive sampling method. Data were collected by distributing questionnaires containing statements to Madu AG consumers. Validity test, reliability test, hypothesis testing using the T and F tests were used in data testing, as well as the coefficient of simultaneous determination using the SPSS 16.0 program. The results prove that partially there is no significant effect between the brand image variable on the Madu AG business families in Tulungagung Regency, likewise on X2 variable partially there is no significant impact between price on the Madu AG business families in Tulungagung Regency. However, in variable X3 partially there is a significant influence between quality product and consumer satisfaction on Madu AG business in Tulungagung Regency. Meanwhile, simultaneously there is a significant influence among the variables brand image, price, and product quality on Madu AG business families in Tulungagung Regency with a contribution of 69.7% and the rest was affected by other unspecified variables